Glass composition, sealing material and sealing material paste

JP2025003302APending Publication Date: 2025-01-09NIPPON ELECTRIC GLASS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024048079
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-03-05
Filing Date
2024-03-25
Publication Date
2025-01-09

AI Technical Summary

Benefits of technology

【0020】 本発明は、良好な耐候性を有しつつ、低温で封着可能なガラス組成物、封着材料及び封着材料ペーストを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025003302000001_ABST
    Figure 2025003302000001_ABST
Patent Text Reader

Abstract

To provide a glass composition, a sealing material and a sealing material paste, capable of sealing at a low temperature while having excellent weather resistance.SOLUTION: A glass composition contains 15-80% TeO2, 0.1-30% MoO3, 5-40% V2O5 and 0.1-10% Nb2O5+MnO+Cr2O3+Fe2O3+Co3O4+NiO in terms of mol.%, as glass components.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass composition, a sealing material, and a sealing material paste that have weather resistance and can be hermetically sealed at low temperatures. [Background technology]

[0002] Sealing materials are used in semiconductor integrated circuits, quartz oscillators, metal members, vacuum insulating glass, flat panel displays, glass terminals for LEDs, etc. Sealing materials are required to have chemical durability and heat resistance, so glass-based sealing materials are used instead of resin-based adhesives. Sealing materials are also required to have properties such as mechanical strength, fluidity, and weather resistance. In particular, sealing electronic components equipped with elements that are sensitive to heat is required to have a sealing temperature as low as possible. Specifically, it is required that sealing can be performed at a temperature of 400°C or less. As glass that satisfies these properties, lead borate glass containing a large amount of PbO, which has a large effect of lowering the softening point, has been widely used (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 63-315536 [Patent Document 2] JP 2019-202921 A Summary of the Invention [Problem to be solved by the invention]

[0004] In order to reduce the environmental impact, it is desirable to replace lead-borate glasses with lead-free glasses that do not contain PbO, and various lead-free glasses with low softening points have been developed.

[0005] However, generally, glass with a low softening point has low weather resistance, which results in problems such as cracks in the glass. Therefore, it is not easy to achieve both a low softening point and high weather resistance. The CuO-TeO2-MoO3-based glass described in Patent Document 2 is a promising candidate to replace lead borate-based glass, and although it has good weather resistance, it cannot be said that its softening point is sufficiently low.

[0006] In view of the above, an object of the present invention is to provide a glass composition, a sealing material, and a sealing material paste that have good weather resistance and can be sealed at low temperatures. [Means for solving the problem]

[0007] As a result of intensive research, the present inventors have found that the above problems can be solved by using a specific TeO2-V2O5-based glass, and propose this in the present invention. Hereinafter, each aspect of the glass composition and the sealing material will be described.

[0008] The glass composition of the first aspect is characterized by containing, in mole percent, 15-80% TeO2, 0.1-30% MoO3, 5-40% V2O5, and 0.1-10% Nb2O5+MnO+Cr2O3+Fe2O3+Co3O4+NiO, where "Nb2O5+MnO+Cr2O3+Fe2O3+Co3O4+NiO" is the total amount of Nb2O5, MnO, Cr2O3, Fe2O3, Co3O4, and NiO.

[0009] The glass composition of embodiment 2 preferably contains, in mol %, 0.1-35% CuO, 0.1-10% Al2O3, 1-30% K2O, and 0-10% PbO, and is substantially free of SeO2, in embodiment 1. Here, "substantially free of SeO2" means that the SeO2 content is less than 0.1 mol %.

[0010] The glass composition of Aspect 3 is the same as that of Aspect 1 or 2, and preferably contains, in mole percent, 0.1 to 15% Li2O+Na2O as a glass composition, and a molar ratio of (Li2O+Na2O) / K2O is 0.05 to 1. Here, "Li2O+Na2O" is the total amount of Li2O and Na2O. "(Li2O+Na2O) / K2O" is the value obtained by dividing the total amount of Li2O and Na2O by the content of K2O.

[0011] The glass composition of Aspect 4 is preferably one of Aspects 1 to 3, and contains, in mole percent, 0.1 to 20% of MgO+CaO+SrO+BaO+ZnO as the glass composition, where "MgO+CaO+SrO+BaO+ZnO" is the total amount of MgO, CaO, SrO, BaO, and ZnO.

[0012] The glass composition of embodiment 5 is any one of embodiment 1 to embodiment 4, and preferably contains, in mol %, La2O3 0-10% and WO3 0-10% as the glass composition.

[0013] The glass composition of embodiment 6 is any one of embodiment 1 to embodiment 5, and preferably contains, in mole percent, SiO20-5%, TiO20-5%, ZrO20-5%, and CeO20-5% as the glass composition.

[0014] The sealing material of the seventh embodiment preferably contains 40 to 100% by volume of a glass powder made of the glass composition of any one of the first to sixth embodiments, and 0 to 60% by volume of a refractory filler powder.

[0015] In the sealing material of embodiment 8, in embodiment 7, the refractory filler powder is preferably substantially spherical. Here, the term "substantially spherical" does not mean only a perfect sphere, but means that the value obtained by dividing the shortest diameter passing through the center of gravity of the refractory filler powder by the longest diameter of the refractory filler powder is 0.5 or more, preferably 0.7 or more.

[0016] In the sealing material of embodiment 9, in embodiment 7 or 8, all or a part of the refractory filler powder is preferably Zr2WO4(PO4)2.

[0017] The sealing material of the tenth aspect is preferably used in any one of the seventh to ninth aspects for a quartz crystal resonator package.

[0018] The sealing material of the eleventh embodiment is preferably used for vacuum insulating glass in any one of the seventh to ninth embodiments.

[0019] The sealing material paste of the twelfth aspect preferably contains the sealing material of any one of the seventh to eleventh aspects and a vehicle. Effect of the Invention

[0020] The present invention can provide a glass composition, a sealing material, and a sealing material paste that have good weather resistance and can be sealed at low temperatures. [Brief description of the drawings]

[0021] [Figure 1] FIG. 2 is a schematic diagram showing a measurement curve obtained by a macro-type differential thermal analyzer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The glass composition of the present invention contains, in mole percent, TeO2 15-80%, MoO3 0.1-30%, V2O5 5-40%, and Nb2O5+MnO+Cr2O3+Fe2O3+Co3O4+NiO 0.1-10%. The reasons for limiting the glass composition range as described above are as follows. In the explanation of the content of each component, "%" means "mol %" unless otherwise specified.

[0023] TeO2 is a component that forms a glass network and improves weather resistance. The content of TeO2 is 15 to 80%, preferably 20 to 70%, 25 to 65%, 30 to 60%, and particularly preferably 40 to 55%. If the content of TeO2 is too low, the glass becomes thermally unstable and is prone to devitrification during melting or firing. On the other hand, if the content of TeO2 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult and tending to cause the thermal expansion coefficient to become too high.

[0024] MoO3 is a component that forms a glass network and reduces the viscosity (softening point, etc.) of glass. The content of MoO3 is 0.1 to 30%, preferably 1 to 20%, 2 to 10%, and particularly preferably 2.5 to 5%. If the content of MoO3 is too low, vitrification becomes difficult and the viscosity (softening point, etc.) of the glass becomes high, making low-temperature sealing difficult. On the other hand, if the content of MoO3 is too high, the glass becomes thermally unstable, the glass becomes easily devitrified during melting or firing, and the thermal expansion coefficient tends to become too high.

[0025] V2O5 is a component that forms a glass network and lowers the viscosity (softening point, etc.) of glass. It is also a component that lowers the thermal expansion coefficient. The content of V2O5 is 5 to 40%, and preferably 7 to 35%, 10 to 30%, 11 to 25%, and particularly 12 to 20%. If the content of V2O5 is too low, vitrification becomes difficult and the viscosity (softening point, etc.) of the glass becomes high, making low-temperature sealing difficult. In addition, the thermal expansion coefficient tends to be too high. On the other hand, if the content of V2O5 is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing.

[0026] Nb2O5 is a component that thermally stabilizes glass and enhances weather resistance. The content of Nb2O5 is preferably 0 to 10%, 0.1 to 10%, 0.5 to 9%, 1 to 7.5%, and particularly preferably 2 to 5%. If the content of Nb2O5 is too low, the glass becomes thermally unstable and is likely to devitrify during melting or firing. In addition, the weather resistance decreases, and as a result, the glass is likely to crack. On the other hand, if the content of Nb2O5 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.

[0027] MnO is a component that thermally stabilizes glass and enhances weather resistance. It is also a component that enhances reactivity with the sealed object. The content of MnO is preferably 0 to 10%, 0.1 to 10%, 0.5 to 9%, 1 to 7.5%, and particularly preferably 2 to 5%. If the content of MnO is too small, the glass becomes thermally unstable and is likely to devitrify during melting or firing. In addition, the weather resistance decreases, and as a result, the glass is likely to crack. On the other hand, if the content of MnO is too large, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.

[0028] Cr2O3 is a component that thermally stabilizes glass and enhances weather resistance. It is also a component that enhances reactivity with the sealed object. The content of Cr2O3 is preferably 0 to 10%, 0.1 to 10%, 0.5 to 9%, 1 to 7.5%, and particularly preferably 2 to 5%. If the content of Cr2O3 is too small, the glass becomes thermally unstable and is likely to devitrify during melting or firing. In addition, the weather resistance decreases, and as a result, the glass is likely to crack. On the other hand, if the content of Cr2O3 is too large, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.

[0029] Fe2O3 is a component that thermally stabilizes glass and enhances weather resistance. It is also a component that enhances reactivity with the sealed object. The content of Fe2O3 is preferably 0 to 10%, 0.1 to 10%, 0.5 to 9%, 1 to 7.5%, and particularly 2 to 5%. If the content of Fe2O3 is too small, the glass becomes thermally unstable and is likely to devitrify during melting or firing. In addition, the weather resistance decreases, and as a result, the glass is likely to crack. On the other hand, if the content of Fe2O3 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.

[0030] Co3O4 is a component that thermally stabilizes glass and enhances weather resistance. It is also a component that enhances reactivity with the sealed object. The content of Co3O4 is preferably 0 to 10%, 0.1 to 10%, 0.5 to 9%, and particularly 1 to 7.5%. If the content of Co3O4 is too small, the glass becomes thermally unstable and is likely to devitrify during melting or firing. In addition, the weather resistance decreases, and as a result, the glass is likely to crack. On the other hand, if the content of Co3O4 is too large, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.

[0031] NiO is a component that thermally stabilizes glass and enhances weather resistance. It is also a component that enhances reactivity with the sealed object. The content of NiO is preferably 0 to 10%, 0.1 to 10%, 0.5 to 9%, and particularly preferably 1 to 7.5%. If the content of NiO is too small, the glass becomes thermally unstable and is likely to devitrify during melting or firing. In addition, the weather resistance decreases, and as a result, the glass is likely to crack. On the other hand, if the content of NiO is too large, the viscosity (softening point, etc.) of the glass increases, and low-temperature sealing is likely to become difficult.

[0032] Nb2O5+MnO+Cr2O3+Fe2O3+Co3O4+NiO (the total amount of Nb2O5, MnO, Cr2O3, Fe2O3, Co3O4 and NiO) is 0.1-10%, preferably 0.5-9%, 1-7.5%, particularly 2-5%. If the amount of Nb2O5+MnO+Cr2O3+Fe2O3+Co3O4+NiO is too small, the glass becomes thermally unstable and the glass is easily devitrified during melting or firing. In addition, the weather resistance is reduced, and as a result, the glass is easily cracked. On the other hand, if the amount of Nb2O5+MnO+Cr2O3+Fe2O3+Co3O4+NiO is too large, the viscosity (softening point, etc.) of the glass becomes high, and low-temperature sealing is easily difficult.

[0033] In addition to the above components, the following components may be incorporated.

[0034] CuO is a component that reduces the viscosity (softening point, etc.) of glass and also reduces the thermal expansion coefficient. In addition, when sealing metal, it is a component that increases the adhesive strength between glass and metal. Although the mechanism for increasing the adhesive strength is unclear at present, it is considered that Cu atoms have high diffusivity, and therefore Cu atoms diffuse from the surface layer of the metal toward the inside, making it easier for glass and metal to be integrated. There is no particular limit to the type of metal to be sealed, and examples include iron, iron alloy, nickel, nickel alloy, copper, copper alloy, aluminum, and aluminum alloy. The content of CuO is preferably 0 to 35%, 0.1 to 35%, 0.2 to 30%, 0.3 to 25%, 0.4 to 20%, 0.5 to 15%, 1 to 12%, and particularly 3 to 11%. If the content of CuO is too low, vitrification becomes difficult, and the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult. In addition, the thermal expansion coefficient tends to be too high. If the CuO content is too high, the glass becomes thermally unstable, and metallic Cu may precipitate on the glass surface during the sealing process, adversely affecting the sealing strength and electrical properties. In addition, the glass becomes easily devitrified during melting or firing.

[0035] Al2O3 is a component that improves weather resistance. The content of Al2O3 is preferably 0 to 10%, 0.1 to 10%, 0.3 to 8%, 0.5 to 6%, and particularly preferably 1 to 4%. If the content of Al2O3 is too low, the weather resistance of the glass decreases, and as a result, the glass becomes more susceptible to cracking. If the content of Al2O3 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.

[0036] Li2O, Na2O and K2O are components that lower the viscosity (softening point, etc.) of glass. The content of Li2O+Na2O+K2O is preferably 0-30%, 1-30%, 5-25%, 7-23%, and particularly preferably 10-20%. If the content of Li2O+Na2O+K2O is too small, the viscosity (softening point, etc.) of the glass increases, which may make sealing at low temperatures difficult. Also, vitrification may be difficult. On the other hand, if the content of Li2O+Na2O+K2O is too large, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Also, the weather resistance is prone to decrease, and the thermal expansion coefficient tends to become too high. The content of Li2O+Na2O is preferably 0-15%, 0.1-15%, 1-12%, and particularly preferably 2-10%.

[0037] Li2O is a component that significantly reduces the viscosity (softening point, etc.) of glass compared to Na2O and K2O. The content of Li2O is preferably 0 to 15%, 0.1 to 15%, 1 to 12%, and particularly preferably 2 to 10%. If the content of Li2O is too low, the viscosity (softening point, etc.) of the glass increases, which may make sealing at low temperatures difficult. Also, vitrification may become difficult. On the other hand, if the content of Li2O is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Also, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.

[0038] Na2O is a component that reduces the viscosity (softening point, etc.) of glass. The content of Na2O is preferably 0 to 15%, 0.1 to 15%, 1 to 12%, and particularly preferably 2 to 10%. If the content of Na2O is too low, the viscosity (softening point, etc.) of the glass increases, which may make sealing at low temperatures difficult. Also, vitrification may become difficult. On the other hand, if the content of Na2O is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Also, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.

[0039] Compared with Li2O and Na2O, K2O is a component that reduces the viscosity (softening point, etc.) of glass without significantly reducing weather resistance. The content of K2O is preferably 0 to 30%, 1 to 30%, 3 to 25%, 5 to 22%, and particularly preferably 10 to 20%. If the content of K2O is too small, the viscosity (softening point, etc.) of the glass increases, which may make sealing at low temperatures difficult. Also, vitrification may become difficult. Furthermore, the weather resistance decreases, and as a result, the glass is more likely to crack. On the other hand, if the content of K2O is too high, the glass becomes thermally unstable and is more likely to devitrify during melting or firing.

[0040] In terms of molar ratio, (Li2O+Na2O) / K2O is preferably 0.05 to 1, 0.08 to 0.6, and particularly preferably 0.1 to 0.3, in order to reduce the viscosity (softening point, etc.) of the glass without significantly reducing the weather resistance.

[0041] PbO is a component that reduces the viscosity (softening point, etc.) of glass. Taking environmental considerations into account, the PbO content is 0 to 10%, preferably 0 to 5%, 0 to 3%, 0 to 1%, and particularly preferably substantially none (less than 0.1%).

[0042] MgO, CaO, SrO, BaO and ZnO are components that broaden the vitrification range and improve weather resistance. MgO+CaO+SrO+BaO+ZnO is preferably 0-30%, 0.1-20%, 1.2-15%, 1.5-12%, and particularly preferably 1.5-5%. If the content of MgO+CaO+SrO+BaO+ZnO is too small, the viscosity (softening point, etc.) of the glass increases, which may make sealing at low temperatures difficult. Also, vitrification may become difficult. On the other hand, if the content of MgO+CaO+SrO+BaO+ZnO is too large, the glass becomes thermally unstable and is easily devitrified during melting or firing. Also, the weather resistance is easily reduced and the thermal expansion coefficient tends to become too high.

[0043] MgO is a component that broadens the vitrification range and improves weather resistance. The content of MgO is preferably 0 to 25%, 0 to 20%, 0 to 10%, and particularly 0.5 to 7%. If the content of MgO is low, vitrification may be difficult. Furthermore, the viscosity (softening point, etc.) of the glass may increase, making sealing at low temperatures difficult. On the other hand, if the content of MgO is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Furthermore, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.

[0044] CaO is a component that broadens the vitrification range and improves weather resistance. The CaO content is preferably 0 to 25%, 0 to 20%, 0 to 10%, and particularly 0.5 to 7%. If the CaO content is low, vitrification may be difficult. Furthermore, the viscosity (softening point, etc.) of the glass may increase, making sealing at low temperatures difficult. On the other hand, if the CaO content is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Furthermore, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.

[0045] SrO is a component that broadens the vitrification range and improves weather resistance. The content of SrO is preferably 0 to 25%, 0 to 20%, 0 to 10%, and particularly 0.5 to 7%. If the content of SrO is low, vitrification may be difficult. Furthermore, the viscosity (softening point, etc.) of the glass may increase, making sealing at low temperatures difficult. On the other hand, if the content of SrO is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Furthermore, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.

[0046] BaO is a component that broadens the vitrification range and improves weather resistance. The content of BaO is preferably 0 to 25%, 0.1 to 20%, 0.5 to 10%, and particularly preferably 1 to 7%. If the content of BaO is low, vitrification may be difficult. Furthermore, the viscosity (softening point, etc.) of the glass may increase, making sealing at low temperatures difficult. On the other hand, if the content of BaO is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing. Furthermore, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.

[0047] ZnO is a component that broadens the vitrification range and improves weather resistance. The content of ZnO is preferably 0 to 25%, 0.1 to 22%, 1 to 20%, and particularly preferably 2 to 15%. If the content of ZnO is too low, vitrification becomes difficult. In addition, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult. On the other hand, if the content of ZnO is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing. In addition, the weather resistance is likely to decrease and the thermal expansion coefficient tends to become too high.

[0048] AgI is a component that reduces the viscosity (softening point, etc.) of glass. The content of AgI is preferably 0 to 3%, 0 to 2%, and particularly preferably 0 to 1%. If the content of AgI is too high, the thermal expansion coefficient tends to be too high.

[0049] SeO2 is a component that reduces the viscosity (softening point, etc.) of glass. Considering the environmental aspect, the content of SeO2 is preferably 0 to 10%, 0 to 5%, 0 to 3%, 0 to 1%, and particularly preferably substantially none (less than 0.1%).

[0050] B2O3 is a component that forms a glass network. The content of B2O3 is 0 to 20%, preferably 0 to 10%, and particularly preferably 0.1 to 5%. If the content of B2O3 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult and making the glass more susceptible to phase separation. Also, vitrification becomes difficult.

[0051] WO3 is a component that reduces the thermal expansion coefficient. The content of WO3 is preferably 0 to 20%, 0 to 10%, 0 to 5%, and particularly preferably 0.1 to 3%. If the content of WO3 is too high, the glass becomes thermally unstable, the glass becomes more likely to devitrify during melting or firing, and the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.

[0052] P2O5 is a component that forms a glass network and thermally stabilizes glass. The content of P2O5 is preferably 0 to 10%, 0 to 5%, 0 to 2%, and particularly preferably 0 to 1%. If the content of P2O5 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult and making the weather resistance easily deteriorate.

[0053] La2O3 is a component that thermally stabilizes glass and suppresses devitrification. The content of La2O3 is preferably 0 to 10%, 0 to 5%, 0 to 2%, and particularly preferably 0.1 to 1%. If the content of La2O3 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.

[0054] SiO2 is a component that thermally stabilizes glass and reduces the thermal expansion coefficient. The content of SiO2 is preferably 0 to 5%, 0 to 2%, and particularly preferably 0.1 to 1%. If the content of SiO2 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.

[0055] TiO2 is a component that thermally stabilizes glass and reduces the thermal expansion coefficient. The content of TiO2 is preferably 0 to 5%, 0 to 2%, and particularly preferably 0.1 to 1%. If the content of TiO2 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.

[0056] ZrO2 is a component that thermally stabilizes glass and reduces the thermal expansion coefficient. The content of ZrO2 is preferably 0 to 5%, 0 to 2%, and particularly preferably 0.1 to 1%. If the content of ZrO2 is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.

[0057] CeO2 is a component that thermally stabilizes glass and reduces the thermal expansion coefficient. The CeO2 content is preferably 0 to 5%, 0 to 2%, and particularly preferably 0.1 to 1%. If the CeO2 content is too high, the viscosity (softening point, etc.) of the glass increases, making low-temperature sealing difficult.

[0058] Ga2O3 is a component that thermally stabilizes glass and also enhances weather resistance, but is very expensive, so its content is preferably less than 0.1%.

[0059] Y2O3, GeO2, and Sb2O3 are components that thermally stabilize glass and suppress devitrification, and each can be added up to less than 5%. If the content of these components is too high, the glass becomes thermally unstable and is prone to devitrification during melting or firing.

[0060] The sealing material of the present invention contains glass powder made of the above glass composition. The sealing material of the present invention may contain a refractory filler powder in order to improve mechanical strength or adjust the thermal expansion coefficient. The mixing ratio is preferably 40 to 100 volume % of glass powder, 0 to 60 volume % of refractory filler powder, 50 to 90 volume % of glass powder, 10 to 50 volume % of refractory filler powder, 55 to 80 volume % of glass powder, and 20 to 45 volume % of refractory filler powder, particularly 60 to 70 volume % of glass powder and 30 to 40 volume % of refractory filler powder. If the content of the refractory filler powder is too high, the ratio of the glass powder becomes relatively small, making it difficult to ensure the desired fluidity.

[0061] The refractory filler powder preferably contains Zr2WO4(PO4)2, which is unlikely to react with the glass powder according to the present invention and has the property of significantly lowering the thermal expansion coefficient of the sealing material.

[0062] In addition, the sealing material of the present invention may use a refractory filler powder other than Zr2WO4(PO4)2 as the refractory filler powder. Other refractory filler powders include NbZr(PO4)3, Zr2MoO4(PO4)2, Hf2WO4(PO4)2, Hf2MoO4(PO4)2, zirconium phosphate, zircon, zirconia, tin oxide, aluminum titanate, quartz, β-spodumene, mullite, titania, quartz glass, β-eucryptite, β-quartz, willemite, cordierite, Sr 0.5 Powders made of Zr2(PO4)3 and the like can be used alone or in combination of two or more kinds.

[0063] The refractory filler powder is preferably substantially spherical. In this way, when the glass powder softens, the fluidity of the glass powder is less likely to be hindered by the refractory filler powder, and as a result, the fluidity of the sealing material is improved. In addition, a smooth glaze layer is easily obtained. Furthermore, even if a part of the refractory filler powder is exposed on the surface of the glaze layer, the stress of this part is dispersed because the refractory filler powder is substantially spherical. As a result, even if the sealed object is in contact with the glaze layer during sealing, undue stress is less likely to be applied to the sealed object, and airtightness is easily ensured.

[0064] Average particle size of refractory filler powder D 50 The average particle diameter D is preferably 0.2 to 20 μm, and more preferably 2 to 15 μm. 50 If the average particle diameter D is too large, the sealing layer tends to become thick. 50 If the average particle diameter D is too small, the refractory filler powder will dissolve into the glass during sealing, making the glass prone to devitrification. 50 " is a value measured on a volume basis and refers to a value measured by a laser diffraction method.

[0065] In the sealing material of the present invention, the softening point is preferably 360° C. or less, 350° C. or less, and particularly preferably 340° C. or less. If the softening point is too high, the viscosity of the glass increases, and the sealing temperature rises, which may cause deterioration of the element due to the heat during sealing. The lower limit of the softening point is not particularly limited, but is practically 180° C. or more. Here, the "softening point" refers to the average particle diameter D 50 The softening point is measured by a macro-type differential thermal analyzer using a sealing material having a thickness of 0.5 to 20 μm as a measurement sample. The measurement conditions are as follows: the measurement is started at room temperature, and the heating rate is 10°C / min. The softening point measured by the macro-type differential thermal analyzer is the temperature (Ts) of the fourth bending point in the measurement curve shown in FIG. 1.

[0066] In the sealing material of the present invention, the thermal expansion coefficient in the temperature range of 30 to 150°C is 20 × 10 -7 / ℃~200×10 -7 / ℃, 30×10 -7 / ℃~160×10 -7 / ℃, 40×10 -7 / ℃~140×10 -7 / ℃, especially 50×10 -7 / ℃~120×10 -7 / ° C. If the thermal expansion coefficient is outside the above range, the difference in thermal expansion with the material to be sealed makes the sealed portion prone to damage during or after sealing.

[0067] Next, an example of a method for producing the glass powder and the sealing material according to the present invention and a method for using the same will be described.

[0068] First, raw material powders prepared to obtain a desired glass composition are melted at 700 to 1000°C for 1 to 2 hours until a homogeneous glass is obtained. Next, the obtained molten glass is formed into a film or the like, and then crushed and classified to produce glass powder. The average particle diameter D of the glass powder is 1.0 mm. 50 The particle size is preferably about 1 to 20 μm. If necessary, various fire-resistant filler powders are added to the glass powder and mixed to prepare a sealing material.

[0069] Next, a vehicle is added to the sealing material and kneaded to prepare a sealing material paste. The vehicle mainly consists of an organic solvent and a resin, and the resin is added to adjust the viscosity of the paste. If necessary, a surfactant, a thickener, etc. can also be added.

[0070] The organic solvent is preferably one that has a low boiling point (for example, a boiling point of 300° C. or less), leaves little residue after firing, and does not alter the glass, and the content is preferably 10 to 40% by mass. As the organic solvent, it is preferable to use propylene carbonate, toluene, N,N'-dimethylformamide (DMF), 1,3-dimethyl-2-imidazolidinone (DMI), dimethyl carbonate, butyl carbitol acetate (BCA), isoamyl acetate, dimethyl sulfoxide, acetone, methyl ethyl ketone, etc. Furthermore, it is more preferable to use a higher alcohol as the organic solvent. Since higher alcohols themselves have viscosity, they can be made into a paste without adding a resin to the vehicle. Furthermore, pentanediol and its derivatives, specifically diethylpentanediol (CH 20 O2) also has excellent viscosity and can be used as a solvent.

[0071] The resin preferably has a low decomposition temperature, leaves little residue after firing, and is less likely to deteriorate the glass, and the content is preferably 0.1 to 20% by mass. As the resin, it is preferable to use nitrocellulose, polyethylene glycol derivatives, polyethylene carbonate, acrylic esters (acrylic resins), etc.

[0072] Next, the sealing material paste is applied to the sealing portions of the objects to be sealed, which are made of metal, ceramic, or glass, using an applicator such as a dispenser or a screen printer, dried, and glazed at 280 to 320° C. Thereafter, another object to be sealed is brought into contact with the sealing material paste and heat-treated at 300 to 400° C., whereby the glass powder softens and flows, and the two are sealed together.

[0073] The glass powder according to the present invention can be used for purposes other than sealing, such as coating and filling, etc. Also, it can be used in a form other than a paste, specifically, in a form such as a powder, a green sheet, or a tablet (a powder material sintered into a predetermined shape). EXAMPLES

[0074] The present invention will be described in detail with reference to examples. Tables 1 and 2 show examples of the present invention (samples Nos. 1 to 10 and 12 to 29) and a comparative example (sample No. 11).

[0075] [Table 1]

[0076] [Table 2]

[0077] [Table 3]

[0078] First, raw material powders prepared to obtain the glass composition shown in the table were placed in a platinum crucible and melted in air at 700 to 1000°C for 1 to 2 hours. The molten glass was then formed into a film using a water-cooled roller, and the film-like glass was crushed in a ball mill and passed through a sieve with 75 μm openings to obtain the average particle diameter D 50 The glass powder obtained was about 10 μm in size.

[0079] Thereafter, the obtained glass powder and the refractory filler powder were mixed as shown in the table to obtain a mixed powder.

[0080] The refractory filler powder used was roughly spherical Zr2WO4(PO4)2 (referred to as ZWP in the table). The average particle diameter D 50 was about 10 μm.

[0081] Samples Nos. 1 to 29 were evaluated for glass transition point, thermal expansion coefficient, softening point, fluidity, and weather resistance.

[0082] The glass transition point and the thermal expansion coefficient in the temperature range of 30 to 150°C were evaluated as follows. First, the mixed powder was placed in a rod-shaped mold and press-molded, and then sintered for 10 minutes at 280 to 350°C on an alumina substrate coated with a release agent. The sintered body was then processed into a specified shape and measured with a TMA device.

[0083] The softening point was measured by a macro-type differential thermal analyzer, and the fourth bending point was taken as the softening point. The measurement was performed in air, the temperature was increased at a rate of 10° C. / min, and the measurement was started from room temperature.

[0084] The fluidity was evaluated as follows. The mass of the mixed powder corresponding to the composite density was placed in a die with a diameter of 20 mm and pressed to obtain a green compact. The green compact was then fired on a glass substrate at 350°C for 10 minutes. Fired bodies with a flow diameter of 19 mm or more were marked with "○", and those with a flow diameter of less than 19 mm were marked with "×".

[0085] Weather resistance was evaluated by an accelerated deterioration test using the PCT (Pressure Cooker Test). Specifically, the fired bodies prepared above were kept in an environment of 121°C, 2 atm, and 100% relative humidity for 24 hours, and then visually observed. Those that had no cracks were rated as "good", and those that had cracks were rated as "bad".

[0086] As is clear from the table, samples No. 1 to 10 and 12 to 29 were evaluated as having good fluidity and weather resistance. On the other hand, sample No. 11 did not contain Nb2O5, MnO, Cr2O3, Fe2O3, Co3O4, or NiO, so it had poor weather resistance and cracks occurred in the fired body. [Industrial Applicability]

[0087] The glass composition of the present invention is suitable for sealing quartz crystal oscillator packages, and is also suitable for sealing airtight packages of semiconductor integrated circuits, flat panel displays, glass terminals for LEDs, aluminum nitride substrates, etc. It can also be used as a sealing material for metals and vacuum insulating glass.

Claims

1. The glass composition is, in mol%, TeO 2 15-80%, MoO 3 0.1-30%, V 2 O 5 5-40%, Nb 2 O 5 + MnO + Cr 2 O 3 +Fe 2 O 3 +Co 3 O 4 + A glass composition containing 0.1 to 10% NiO.

2. The glass composition is, in mole percent, CuO 0.1 to 35%, Al 2 O 3 0.1-10%, K 2 O 1-30%, PbO 0-10%, and essentially SeO 2 2. The glass composition according to claim 1, which is free of:

3. The glass composition is, in mol%, Li 2 O+Na 2 O 0.1 to 15%, in a molar ratio of (Li 2 O+Na 2 O) / K 2 3. The glass composition according to claim 1, wherein O is 0.05 to 1.

4. 3. The glass composition according to claim 1, comprising, in mol %, 0.1 to 20% of MgO+CaO+SrO+BaO+ZnO.

5. The glass composition is, in mol%, La 2 O 3 0-10%, WO 3 3. The glass composition according to claim 1, further comprising 0 to 10% of ZnO.

6. The glass composition is, in mol%, SiO 2 0-5%, TiO 2 0-5%, ZrO 2 0-5%, CeO 2 3. The glass composition according to claim 1, further comprising 0 to 5% of ZnO.

7. 3. A sealing material comprising 40 to 100% by volume of a glass powder made of the glass composition according to claim 1 or 2, and 0 to 60% by volume of a refractory filler powder.

8. 8. The sealing material according to claim 7, wherein the refractory filler powder is substantially spherical.

9. The refractory filler powder is entirely or partially Zr 2 WO 4 (P.O. 4 ) 2 The sealing material according to claim 7 ,

10. 8. The sealing material according to claim 7, which is used for a quartz crystal oscillator package.

11. 8. The sealing material according to claim 7, which is used for vacuum insulating glass.

12. A sealing material paste comprising the sealing material according to claim 7 and a vehicle.

Citation Information

Patent Citations

  • Frit for low-temperature sealing

    JP1988315536A

  • Glass composition and sealing material

    JP2019202921A